PENGARUH MACAM PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI SENDOK (Brassica rapa subsp.): Kata kunci: Sawi, pupuk kandang, dan pertumbuhan - Wahyu Hidayatulloh; Siswadi, Siswadi; Ratna Nurhayati, Dewi (innofarm, 2023)
The research "The Effect of Types of Fertilizers on the Growth and Yield of Mustard' (Brassica rapa subsp.)" was carried out from 1 August to 4 September 2022 at Green House Suhargo Farm, Wates Village, Ngrampal District, Sragen Regency, has a brown latosol soil type and is at an altitude 296 meters above sea level. The purpose of this study was to examine the effect of various forms of manure on the growth and yield of mustard plants, as well as the dosage and type of fertilizer that gave the highest yields for mustard plants. (Brassica rapa subsp.). This study used a completely randomized design (CRD) with a single factor, namely the type of manure. The first treatment applied in this experiment was broiler kohe fertilizer, at the first level using doses of A1 = 16.98 g/polybag, A2 = 22.96 g/polybag, A3 = 50.94 g/polybag. For the second treatment, the administration of cow kohe fertilizer at a dose of S1 = 5.65 g/polybag, S2 = 11.30 g/polybag, and S3 = 16.95 g/polybag. The last treatment was giving kohe goat fertilizer at a dose of G1 = 11.30 g/polybag, G2 = 22.60 g/polybag, and G3 =33.90 g/polybag. Each treatment was repeated three times, resulting in 27 polybags with two plants per growing medium. To find out the results of each treatment, this study used ANOVA, then for further testing of the data the BNJ test at 5% level was used. The results of this study were that the manure treatment did not affect all plant characteristics including plant height, leaf length, leaf width, number of leaves, root length, plant dry weight, and fresh weight of mustard greens (Brassica rapa subsp.).The A2 treatment gave the best results on the parameters of plant height (20.50 cm), leaf length (15.67 cm), and leaf width (8.00 cm). G1 treatment gave the best results on the number of leaves (14.00), fresh weight (12.00 grams), and dry weight (13.56 grams). Keywords: Sawis, manure, and growth e